- بناء نموذج تنظيمي للاعتماد المدرسي من المنظور التربوي الإسلامي: مدارس التعليم ما بعد الأساسي بسلطنة عمان أنموذجا: Building an Organizational Model for School Accreditation from an Islamic Educational Perspective: Post-basic education schools in the Sultanate of Oman as a Model. - AL-RUQAISHI, BADRIA; Jamil, Asyraf Israqi; Mohamed Adnan, Mohamad Azrien (Online Journal of Research in Islamic Studies, 2022)
Research Objectives: The research aims to build a model according to standards and indicators for school accreditation for schools of post-basic education in the Sultanate of Oman from an Islamic educational perspective that is compatible with the nature of the educational system in the Sultanate. To be a guide and guide for those in charge of improving and developing school performance, since school accreditation is one of the modern systems prevailing globally in evaluating the performance of global institutions. Study Methodology: The study relies on the descriptive approach, collecting information and literature on international and Arab school accreditation standards and linking them to the Islamic perspective. Results: The researcher designed a special school accreditation model for post-basic education consisting of (12) criteria distributed over (94) main indicators. Based on the need analysis and review of the main dimensions used in the previous studies, and for the purpose of sorting out the educational efficiency criteria for the school in the Ministry of Education in the Sultanate of Oman, these dimensions were framed in (12) main criteria. The originality of the research: The school accreditation system is one of the educational systems that studies have agreed upon is an urgent and necessary need for schools to ensure the quality of outputs and reassure the community that the school is doing its job to the fullest. And recommended the need to apply it in educational institutions. Which recommended that accreditation should not be limited to institutions of higher education and private education alone, but should be extended to include the education system in all its stages and institutions. Hence the necessity of conducting this study, due to the lack of accurate standards that enable us to measure the efficiency of the school, through an evaluation program based on well-studied global scientific foundations and in line with the environment, Omani society and the nature of the stage and characteristics of post-basic education.